2013
DOI: 10.1371/journal.pone.0070342
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Cone Opsins in Distinct Photoresponses of Intrinsically Photosensitive Dermal Chromatophores in Tilapia Oreochromis niloticus

Abstract: Dermal specialized pigment cells (chromatophores) are thought to be one type of extraretinal photoreceptors responsible for a wide variety of sensory tasks, including adjusting body coloration. Unlike the well-studied image-forming function in retinal photoreceptors, direct evidence characterizing the mechanism of chromatophore photoresponses is less understood, particularly at the molecular and cellular levels. In the present study, cone opsin expression was detected in tilapia caudal fin where photosensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 68 publications
(71 reference statements)
2
34
0
Order By: Relevance
“…Interestingly, it has recently been observed that opsins are also expressed in a variety of non-eye tissues of fishes including the skin, where they are thought to mediate colour change via chromatophore light sensing (e.g. Chen et al, 2013;Davies et al, 2015). Whether the dottybacks also express opsins in their skin and how light sensing may contribute to colour change in this species warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has recently been observed that opsins are also expressed in a variety of non-eye tissues of fishes including the skin, where they are thought to mediate colour change via chromatophore light sensing (e.g. Chen et al, 2013;Davies et al, 2015). Whether the dottybacks also express opsins in their skin and how light sensing may contribute to colour change in this species warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, extraocular photoreceptors can also express opsins identical to those in the retina and may potentially use visual phototransductive pathways. Examples of these include rhodopsin in the light organ and parolfactory vesicles of squids and cone opsins in the dermis of fish (Hara and Hara, 1980;Tong et al, 2009;Ban et al, 2005;Kasai and Oshima, 2006;Chen et al, 2013). Nile tilapia (Oreochromis niloticus) and neon tetra (Paracheirodon innesi) are particularly notable, because opsins identical to those in the retina play a role in initiating signals that result in expansion and contraction of pigment cells (chromatophores) or modulation of the color reflected from iridophores.…”
Section: Introductionmentioning
confidence: 99%
“…neurohormones) or external stimuli (e.g. light), chromatophores are able to make rapid, remarkable colour changes (Mäthger et al, 2003;Ban et al, 2005;Chen et al, 2013;Nilsson Sköld et al, 2013). For example, intrinsically photosensitive dermal chromatophores of the Nile tilapia Oreochromis niloticus demonstrate distinct photoresponses (Chen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…light), chromatophores are able to make rapid, remarkable colour changes (Mäthger et al, 2003;Ban et al, 2005;Chen et al, 2013;Nilsson Sköld et al, 2013). For example, intrinsically photosensitive dermal chromatophores of the Nile tilapia Oreochromis niloticus demonstrate distinct photoresponses (Chen et al, 2013). Independent of wavelength, the black pigments (melanosomes) of melanophores tend to disperse and melanophores maintain dispersion state by shuffling pigment granules (Chen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation